MENELAAH BENTUK KONSEPSI PEMBELAJARAN ONLINE DAN BLENDED LEARNING DI MASA NEW NORMAL MENUJU ERA METAVERSE - Zubaidi, Zubaidi; Rahman Untoro, Aldi (Institut Daarul Qur'an Jakarta, Indonesia, 2022)
The research uses a type of literature study research by collecting data from several related journals according to the research focus. The results of this study are presented in the form of a descriptive, structured and systematic conceptual explanation. Various challenges and online learning strategies that require and require teachers to innovate and adapt well. In the new normal era, teachers need to design curriculum for learning materials to be delivered during online learning meetings with Zoom, Google Meet, Teachmint, and others. Teachers are required to adapt and develop themselves to face various complex educational challenges. There are several strategic steps for online learning methods in the new normal, namely 1.) Creating learning targets by aligning the conditions in the new normal, 2.) Identifying the resources needed and owned to achieve the new goals set, 3.) Mapping the situation of conditions for teachers and students to prepare to use the blended learning method, 4.) Assessing the gap between needs and availability as material for preparing strategic and operational steps, 5.) Executing these steps innovatively and creatively by establishing various partnerships with various external parties who care about education. Of course, these various strategic steps need to be carefully planned, then analyzed and evaluated before being applied in learning activities.